ANALYSIS OF THE EFFECT OF UNMET NEED FOR FAMILY PLANNING ON UNINTENDED PREGNANCY AT PANTI WILASA CITARUM HOSPITAL SEMARANG - Ratnaningsih, Ester (Jurnal Kebidanan, 2018)
Unmet need for family planning is defined as the percentage of women of reproductive age ,either married  or in a union, who want to stop or delay childbearing until 24 months but are not using any method of contraception to prevent pregnancy.Unmet need for family planning is a multidimentional  problem because it is influenced  on various  factors. Unmet need for family planning rate at Central Java in 2015 was 10,48%.This study aims to determine relationship between the incidence of unmet need for family planning and unintended  pregnancy.This study was ananalytic  survey with cross-sectional design. This study was  conducted among pregnant women who did not use any contraception method at Panti Wilasa Citarum Hospital Semarang in September-December 2017. The study samples were pregnant women as many as 92. Study instrument used here was aquestionnaire about unmet need for family planning, pregnancy and women knowledge on the types of contraception /family planning method which contained 20 questions.The results showed that 25 women (27,2%) were pregnant because they did not use any contraception method. The results indicated that unmet need for family planning had an effect on unintended pregnancy (p=0.001). There were effects of age, number of children and knowledge about the types of contraception /family planning method on unintended pregnancy. There was no significant correlation between education  with unintended pregnancy (p-value>0.05).It can be concluded that unmet need for family planning had a correlation with unintended pregnancy.